The Effect of Above-Ground Medium Voltage Power Lines on Displaying Site Selection of the Great Bustard (Otis Tarda) in Central Hungary - Lóránt Miklós (Sciendo, 2014)
Our study was conducted in the Upper-Kiskunság region, Central Hungary, which hosts the largest Pannonian population of the Great Bustard (Otis tarda). The influence of the presence of aboveground medium voltage power lines on displaying site selection of Great Bustard males was investigated. The results revealed that displaying males totally reject the sites located within 350-400 m or closer to medium voltage power lines as displaying sites and show relative rejection towards potential displaying sites located at a distance between 500 and 1000 m far from power lines. Surprisingly, the overall negative effects influence much larger part of the potential displaying grounds, up to the distance to 3500 m from power lines. It can be declared that power lines reduce the extent of suitable displaying sites of the Great Bustards in the Upper-Kiskunság region. Accordingly, installation of new above-ground power lines (and other kind of wires, such as high voltage power lines, optical cables etc.) would further reduce the extent of suitable displaying sites.